2014
DOI: 10.1002/jnr.23506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth factors and steroid hormones on heme oxygenase and cyclin D1 expression in primary astroglial cell cultures

Abstract: Astrocyte activity may be modulated by steroid hormones and GFs. This study investigates the interaction between glucocorticoids or estrogens and GFs on the expression of heme oxygenase-1 (HO-1) and cyclin D1 in astrocyte cultures at 14 days treated for 48 or 60 hr with dexamethasone (DEX) or 48 hr with 17β-estradiol (E2) alone or with GFs added only in the last 12 or 24 hr. Twelve- or twenty-four-hour epidermal growth factor (EGF) treatment significantly enhanced HO-1 expression in astrocyte cultures pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…β‐Actin monoclonal antibody (clone [AC‐15]: antibody ID: AB_367161; antibody name: β‐actin antibody [AC‐15]; antibody target: β‐actin antibody [AC‐15]; vendor: GeneTex [Irvine, CA; catalog No: GTX26276]; clonality: monoclonal antibody; clone ID: clone AC‐15; host organism: mouse; Proper Citation: GeneTex [catalog No. GTX26276; RRID: AB_367161]) recognized a single band of 42 kDa molecular weight on Western blots of rat brain (manufacturer's data sheet) and stained a pattern of cellular morphology and distribution identical to that in our previous studies (Bramanti et al, ). Staining was eliminated by preincubation of the diluted antiserum (1:2,000) with 30 µg/ml of the recombinant protein.…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations
“…β‐Actin monoclonal antibody (clone [AC‐15]: antibody ID: AB_367161; antibody name: β‐actin antibody [AC‐15]; antibody target: β‐actin antibody [AC‐15]; vendor: GeneTex [Irvine, CA; catalog No: GTX26276]; clonality: monoclonal antibody; clone ID: clone AC‐15; host organism: mouse; Proper Citation: GeneTex [catalog No. GTX26276; RRID: AB_367161]) recognized a single band of 42 kDa molecular weight on Western blots of rat brain (manufacturer's data sheet) and stained a pattern of cellular morphology and distribution identical to that in our previous studies (Bramanti et al, ). Staining was eliminated by preincubation of the diluted antiserum (1:2,000) with 30 µg/ml of the recombinant protein.…”
Section: Methodsmentioning
confidence: 52%
“…Some findings (Dhandapani and Brann, 2003) support a role for astrocytes in neuroprotection and raise the intriguing possibility that astrocytes might help to mediate the neuroprotective effect of 17b-estradiol (17b-E 2 ) in an in vitro model. GFs, such as basic fibroblast growth factor (bFGF), EGF, IGF-I, and INS, act as mitogenic peptides and participate in neuron-glia cross-talk, stimulating cultured nerve cell proliferation and differentiation (Bramanti et al, 2015). In particular, GFs play a pivotal role in the dynamic flow of signaling molecules between neurons and astroglia (Avola et al, 2000;Bramanti et al, 2015).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…As a candidate which is regulated its expression by CORT, cyclin-related proteins, such as cyclin D1, D3, cyclin-dependent kinase 4 or 6, might play a role here, since they are related to cell proliferation and their function is modulated by glucocorticoid. [33][34][35] In conclusion, we demonstrated that CORT inhibited the proliferation of C6 glioma cells via GR, but not MR, by using their respective antagonists, mifepristone and spironolactone. In addition, this inhibitory effect of cell proliferation was unrelated to apoptosis or mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 60%
“…They are the most abundant glial cells in the brain that are closely associated with neuronal synapses [1]. Glial cells are also involved in providing neurotrophic signals to neurons required for their survival, proliferation, and differentiation [2]. In addition, reciprocal interactions between glia and neurons are essential for many critical functions in brain health and disease.…”
Section: Introductionmentioning
confidence: 99%